Alcohol Use Among Latino Males - Colon, Edgar (Alcoholism Treatment Quarterly, 1998)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-066-382-277-325, pop00295 tex.type: [object Object]
Keywords: alcoholism; article; dept.swk; ethnic group; health care delivery; health care planning; human; incidence; preventive health service; united states